2014
DOI: 10.1089/jop.2013.0050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypotonic 0.18% Sodium Hyaluronate Eyedrops on Inflammation of the Ocular Surface in Experimental Dry Eye

Abstract: Hypotonic 0.18% SH eyedrops are more effective in improving ocular surface irregularity and staining and decreasing inflammatory cytokines, chemokines, and cells on the ocular surface compared with isotonic 0.5% CMC or 0.1% SH eyedrops in the treatment of EDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…Both IL-1b and IL-6 are proinflammatory cytokines that are secreted on the ocular surface in response to various pathogenic stimuli, such as benzalkonium chloride-induced EDE, desiccant stressinduced EDE, and microbial infections, such as Pseudomonas aeruginosa, Onchocerca volvulus, and herpes simplex virus 1. 35,48,49 Interleukin-6, along with other proinflammatory cytokines, has a major role in the pathogenesis of several inflammatory diseases, including DED, graft-versus-host disease, and thyroid-associated ophthalmopathy through the NFjB and MAPK pathways. 50,51 In addition, previous studies have shown that increased expression of IL-1b during ocular surface inflammation induces the loss of corneal epithelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IL-1b and IL-6 are proinflammatory cytokines that are secreted on the ocular surface in response to various pathogenic stimuli, such as benzalkonium chloride-induced EDE, desiccant stressinduced EDE, and microbial infections, such as Pseudomonas aeruginosa, Onchocerca volvulus, and herpes simplex virus 1. 35,48,49 Interleukin-6, along with other proinflammatory cytokines, has a major role in the pathogenesis of several inflammatory diseases, including DED, graft-versus-host disease, and thyroid-associated ophthalmopathy through the NFjB and MAPK pathways. 50,51 In addition, previous studies have shown that increased expression of IL-1b during ocular surface inflammation induces the loss of corneal epithelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…35 Briefly, the conjunctival tissues were collected (five eyes per group), pooled in a lysis buffer containing protease inhibitors, and incubated for 30 minutes. The cell extracts then were centrifuged at 14,000g at 48C for 15 minutes, and the supernatants were stored at À708C until use.…”
Section: Multiplex Immunobead Assay For Inflammatory Cytokines and Chmentioning
confidence: 99%
“… 9 In addition, HA has been shown to modulate the inflammatory response. 10 More recently, osmoprotectants erythritol, L-carnitine and glycerine have been added to CMC 11 to reduce the cellular stress level of the ocular surface, 12 , 13 but to date, these ingredients have not been combined with HA.…”
Section: Introductionmentioning
confidence: 99%
“…The goblet size density in conjunctiva was high on administration of 0.3% HA and 0.18%HA compared to 0.1% HA. The inflammation on the ocular surfaces decreases with increase in the goblet size [28]. Thus 0.3% HA was most effective when compared to 0.18% and 0.1% HA in the treatment of dry eye disease.…”
Section: Thermosensitive Atelocollagen Punctal Plugmentioning
confidence: 96%
“…Hyaluronic acid based eye drops are coated around the corneal endothelium since it offers a lubricating effect and also offers resistance to dehydration, effectively binds to water and has good biocompatibility [18,19]. Artificial tear eye drops of HA can be used to stabilize the preocular tear film, improve the irregularity on the ocular surface and reduce the symptoms of dry eye [20][21][22]. A study was done to compare the efficacy of preservative free 0.1% HA, 0.18% HA and 0.3% HA artificial tear drops in the mouse model withering stress induced environmental and pharmacological experiment in dry eye disease.…”
Section: Hyaluronic Acid Based Eye Dropsmentioning
confidence: 99%